Sport in the process of education - Jolanta Elżbieta Kowalska (Kazimierz Wielki University, 2018)
The study has highlighted the issue of sport in terms of its place and role in the process of education. The author draws attention to selected aspects: athletes as role models in moral education, ethical factors in sport, sports spectacle or the European football championship. The author points to the enormous potential of sport in supporting the process of education, while stressing that it should be used in a well thought out and planned.